PRIVATIZATION OF WAR: THE CHALLENGES AND THE QUESTION OF FLEXIBILITY FOR THE ARMY - Mile Kostoski (Bezbednosni Dijalozi, 2023)
The paper focuses on the contemporary trend of privatization of security and warfare. Increasingly, the states set regulations for the engagement of private military companies (PMCs) in various military services in exchange for financial compensation. This paper treats PMCs as non-state actors regulated by the state in which they are registered but with missions designated to foreign states. The main premise is that the privatization of warfare and PMCs nevertheless create great challenges for the traditional understanding of the state-run governance of the military sphere. Consequently, it is a challenge for the conduct of global security and foreign policy in general. In this analysis, we contextualize the research problem and analyse it through the Macedonian prism. The academic community, as well as the practitioners, have not detected this problem yet, mostly because the state does not allow the formation of PMCs yet. We argue that that position is one-sided because the global trend of privatization of warfare and military services affects all states through the logic of a market for a force that disregards state borders and regulations. Therefore, an attempt is made to get insights into the question of how the privatization of warfare affects the reform processes as well as the military staff of the Macedonian Army.